Invisible - Patterson, James 1947-; Ellis, David; LaVoy, January; Collins, Kevin T.; Smith, Cheryl; O'Connell, Jared; Hachette Audio (Firm) (New York : Hachette Audio, 2014)
Emma Dockery is obsessed with finding a link between the unsolved cases that number in the hundreds. So obsessed she has taken a leave from the FBI, has covered her bedroom walls with the newspaper clippings, and has recurring nightmares. No one believes her when she says they are all connected, until she finds evidence that cannot be ignored. More crimes happen without explanation, motives, weapons, or suspects. Could only one person really be to blame for all of them?
Keywords: United States -- Federal Bureau of Investigation -- Fiction -- Officials and employees; Government investigators -- Fiction; Suspense fiction; Audiobooks